Chimpanzee (Pan troglodytes) material culture: implications on taxonomy - Campanacho, Vanessa (2008)
In this paper it is suggested a review of the current taxonomy of the chimpanzee (Pan troglodytes). Based on the material culture, and others factors, such as genetic information, it is argued the inclusion in the genus Homo. There are several references concerning the use of tools by chimpanzees, which all together show that, after man, they exhibit the biggest repertory of tools. The use of tools is not innate, it is learned and socially transmitted between generations. Not all chimpanzee populations exhibit the same range of tools, demonstrating the present of a material culture, when an ecological explanation is lacking. The manipulation of tools may indicates the existence of complex cognitive capacities. The genus Homo is characterized by a large cranial capacity, bipedal locomotion, language, related possession of human-like precision grip, construction and manipulation of tools. This study discusses these criteria applied to the case of the chimpanzees.